Toward Dynamic Magnetic Resonance Imaging of the Vocal Tract During Speech Production - Ventura, Sandra Rua (2021)
The most recent and significant magnetic resonance imaging (MRI) improvements allow for the visualization of the vocal tract during speech production, which has been revealed to be a powerful tool in dynamic speech research. However, a synchronization technique with enhanced temporal resolution is still required.